The role of insulin signaling with FOXO and FOXK transcription factors - Masaji Sakaguchi (Endocrine Journal)
Insulin is an essential hormone for animal activity and survival, and it controls the metabolic functions of the entire body. Throughout the evolution of metazoan animals and the development of their brains, a sustainable energy supply has been essential to overcoming the competition for survival under various environmental stresses. Managing energy for metabolism, preservation, and consumption inevitably involves high oxidative stress, causing tissue damage in various organs. In both mice and humans, excessive dietary intake can lead to insulin resistance in various organs, ultimately displaying metabolic syndrome and type 2 diabetes. Insulin signals require thorough regulation to maintain metabolism across diverse environments. Recent studies demonstrated that two types of forkhead-box family transcription factors, FOXOs and FOXKs, are related to the switching of insulin signals during fasting and feeding states. Insulin signaling plays a role in supporting higher activity during periods of sufficient food supply and in promoting survival during times of insufficient food supply. The insulin receptor depends on the tyrosine phosphatase feedback of insulin signaling to maintain adipocyte insulin responsiveness. α4, a regulatory subunit of protein phosphatase 2A (PP2A), has been shown to play a crucial role in modulating insulin signaling pathways by regulating the phosphorylation status of key proteins involved in these pathways. This short review summarizes the current understanding of the molecular mechanism related to the regulation of insulin signals.